A case report of anaphylaxis after contact with raw potato in a 4-year-old boy (Indian Journal of Case Reports, 2020)
Although white potato is very common nutrition, allergic reactions to potato are rarely seen and allergy to uncooked potato has been reported mainly in adults. In this article, we present the case of a 4-year-old male patient who admitted to the Emergency Unit with complaints of urticaria, angioedema, and vomiting. The boy was just playing with raw potatoes just before the onset of his complaints. Therefore, tests were performed with uncooked potato and found to be positive. Our case points towards the importance of heat-labile allergens. Even the patient is able to eat a cooked form of suspicious food, tests for the raw form of the same food must be conducted.